Intercalation of water and guest molecules within Ca2+-Montmorillonite - Halim, N.A.; Ibrahim, Z.A.; Ahmad, A.B. (Kluwer (now part of Springer), 2010)
The high potential for intercalations by water and various guest molecules is induced by the exchangeable cation inside Ca2+-Montmorillonite gallery. XRD peak for Mon at 2 theta = 6.04A degrees (d (001) = 1.462 nm) shows the structural effect on the clay gallery influenced by the intercalated water layers. Further increases in the gallery height are observed with the intercalation of octadecyl ammonium cations in OMON (d (001) = 1.840 nm) and ENR-50 matrix chains in CENR-50 (d (001) = 1.954 nm). DSC studies on the other hand reveal the thermal behaviors of intercalated molecules that are linked to the exchangeable cations. The endothermic of Ca2+-Montmorillonite (H (Mon) = 356.3 J/g) in low temperature range (30-100 A degrees C) indicates the removal of free water and hydrogen bonded water molecules, while the endothermic around 150 A degrees C is related to the induced skeletal layer of water within Ca2+-Montmorillonite. The OMON endothermic (H (OMON) = 47.0 J/g, T (m) = 36.94 A degrees C) tells that cation exchange had modified the water structures and content inside the renewed clay. The intercalation of ENR-50 chains into OMON gallery reveals two endothermic with the T (m1) and T (m2) are at 86.24 and 113.80 A degrees C, respectively. These T (m)s confirm that the alkyl chain segment on octadecyl ammonium cation occupy the OMON interlayer space.